Hm..I'm pretty sure the answer is 34
Answer:
(a + 2b)(a - b)
Step-by-step explanation:
Assuming you require the expression to be factored
Given
a² +
ab - b² ← factor out
from each term
=
(a² + ab - 2b²) ← factor the quadratic
Consider the factors of the coefficient of the b² term(- 2) which sum to give the coefficient of the ab- term (+ 1)
The factors are + 2 and - 1, since
2 × - 1 = - 2 and 2 - 1 = + 1, thus
a² + ab - 2b² = (a + 2b)(a - b) and
a² +
ab - b² =
(a + 2b)(a - b)
Answer:
16
Step-by-step explanation:
Answer:
D. (x-5)^2 = 36
Step-by-step explanation:
If you add 11 to the given equation, you get ...
x^2 -10x = 11
Then you can add the square of half the x-coefficient to complete the square.
x^2 -10x +25 = 11 +25
(x -5)^2 = 36 . . . . simplify to the appropriate form